The influence of food symbolism on food insecurity in South Africa how relevant is the eucharistic celebration? - Byarugaba, George (2017)
Various research results point out poverty, inadequate food production and inadequate distribution as the main culprits for food insecurity in many African countries. This article wishes to contribute to the existing knowledge on food insecurity and concentrate on South Africa and investigate whether food symbolism can also lead to systematic food insecurity and discrimination of some people. Since the official end of political apartheid in 1994, there have been great improvements in terms of grants, aid, increase in food production and change of structures. Nevertheless, food insecurity still persists. This research seeks to uncover new facts concerning the cause for food insecurity in South Africa. It brings to the fore that instead of focusing on structural changes only, researchers need to re-evaluate some of the cultural and religious beliefs attached to food production, distribution and consumption. The article also hopes to highlight that the Eucharist which is a centre of Christian life ought to unite the faith-based communities and confront the vice of injustice in all its forms which exacerbates the problem of food insecurity. Christian encounter with Christ through the Eucharist forms the believers into a community of brothers and sisters and empowers people to participate in the liberating mission of the Lord. This solution would go to the roots of the moral problem of food insecurity and put institutions and structures on a new, more humane and beneficial foundation.
Keywords: Contestations; Eucharist; Food insecurity; Symbolism